Super-high tumor mutational burden predicts complete remission following immunotherapy: from Peto’s paradox to druggable cancer hallmark - Ming Zheng (Journal for ImmunoTherapy of Cancer)
Background The somatic mutation theory predicts that cancer risk should scale proportionally with lifetime cell divisions; yet large-bodied and long-lived species exhibit lower-than-expected cancer incidence—a long-standing contradiction termed Peto’s paradox. Resolving this paradox and clarifying how tumor mutational burden (TMB) shapes treatment response to immune-checkpoint inhibitor (ICI) therapy remain unmet needs in precision oncology.Methods This study analyzed three data streams: (1) human cancer incidence data from North American registries; (2) cancer mortality records for 110,148 mammals (191 species) linked to body mass, life expectancy, and cancer risk, and (3) >30,000 tumors profiled in three independent pan-cancer cohorts and clinical outcomes in >2,700 ICI-treated patients. A digital-medicine approach using 1,000 bootstraps was employed to generate digital randomized cohorts for internal validation, with clinicogenomic covariates matched to mirror real-world clinical features.Results (1) Both cancer incidence and mutational accumulation are age-coupled in humans (p<0.001), sharply rising after age 40. (2) Across species, cancer risk correlates strongly with somatic mutation rate and lifetime mutational burden (rho>0.6), but not with body size or life expectancy (rho<0.2), quantitatively resolving Peto’s paradox. (3) TMB coherently increases with patients’ age across The Cancer Genome Atlas, OrigiMed, and Memorial Sloan Kettering (MSK) cohorts, independent of TMB-detection assays (all p<0.001). (4) In ICI-treated patients, higher TMB confers dose-dependent improvement in overall and progression-free survival and objective response rate. A “super-high” TMB threshold (>25 mut/Mb via MSK-Integrated Mutation Profiling of Actionable Cancer Targets or FoundationOne test) markedly enriched complete remissions (~8-fold increase), validated consistently in both real-world independent cohorts and digital randomized cohorts.Conclusions Somatic mutational accumulation emerges as a unifying determinant of cancer risk in human and non-human species, resolving Peto’s paradox and redefining TMB as a clinically actionable cancer hallmark. Quantifying TMB stratifies immunotherapy efficacy dose-dependently, with super-high TMB predicting durable tumor eradication; thus, therapeutically boosting neoantigen load in low-TMB tumors may convert ICI non-responders to responders. By proposing a universal framework—“cancer disease continuum”—unified by mutational burden as a shared hallmark across tumor initiation, progression, and immunogenicity, this study recasts mutational burden as both a biological price of longevity and an Achilles’ heel exploitable for durable, complete tumor remission in personalized medicine.